Problemas de contagem no ensino fundamental : uma experiência com tarefas exploratório-investigativas e registros de representação semiótica - Lara, Wanderson Mendes de (2017)
This research was started because of concerns regarding the teaching and learning of Counting Problems in Elementary School. With the intent of contributing to the construction of basic Combinatorial concepts, we elaborated exploratory-investigative tasks and we tried through these tasks, to analyze the answers that were made by students of an 8th grade of Elementary School, in order to answer the following investigative question: what learning occurs with the mobilization of registers of semiotic representation theory to do counting in a scenario of exploratory- investigative tasks in an 8th grade of Elementary School? The theoretical and methodological reference is constituted by the registers of semiotic representation theory propounded by Duval; by the theory of Mathematical Investigations, Ponte et al. Besides that the research also had the collaboration of Pessoa and Borba. We present a brief historical retrospective on the subject, besides a previous analysis of other works in the area and official documents aimed at teaching and learning of Mathematics subject regarding to contents of Counting Problems in Elementary School. The research was developed with a group of 25 students of the 8th grade Elementary School in a public school in São Paulo state, in the year 2016. The data collection was done through field notes (logbook), and from the records written by the students during the development of the sequence of tasks. Through this investigation, we could verify that the study of Counting Problems through exploratory-investigative tasks allows the articulation of different registers of semiotic representation, leading to a better understanding of this topic.